Karl Polanyi and twenty-first century socialism - Block, Fred (openDemocracy, 2016)
Polanyi’s views were the exact opposite of his contemporary, Joseph Schumpeter, who famously defined democracy as giving people a choice over which elite group would rule over them.
Sociology
Keywords: socialism

Karl Polanyi for President - Iber, Patrick; Konczal, Mike (Dissent Magazine, 2016)
Are you a Bernie Sanders supporter? Chances are you'll like Karl Polanyi, too. An explainer.
N/A
Keywords: Great Transformation; The (Book); SANDERS; Bernie

Polanyi In Our Times - Saval, Nikal (The Nation, 2016)
N/A
Keywords: Greek crisis; biography; blog